Function-altering SNPs in the human multidrug transporter gene ABCB1 identified using a Saccharomyces-based assay. - Hotcherl Jeong; Ira Herskowitz; Deanna L Kroetz; Jasper Rine (PLoS Genetics, 2007)
The human ABCB1 (MDR1)-encoded multidrug transporter P-glycoprotein (P-gp) plays a major role in disposition and efficacy of a broad range of drugs including anticancer agents. ABCB1 polymorphisms could therefore determine interindividual variability in resistance to these drugs. To test this hypothesis we developed a Saccharomyces-based assay for evaluating the functional significance of ABCB1 polymorphisms. The P-gp reference and nine variants carrying amino-acid-altering single nucleotide polymorphisms (SNPs) were tested on medium containing daunorubicin, doxorubicin, valinomycin, or actinomycin D, revealing SNPs that increased (M89T, L662R, R669C, and S1141T) or decreased (W1108R) drug resistance. The R669C allele's highly elevated resistance was compromised when in combination with W1108R. Protein level or subcellular location of each variant did not account for the observed phenotypes. The relative resistance profile of the variants differed with drug substrates. This study established a robust new methodology for identification of function-altering polymorphisms in human multidrug transporter genes, identified polymorphisms affecting P-gp function, and provided a step toward genotype-determined dosing of chemotherapeutics.